In Search of the State? Neoliberalism and the labour question for pan-African feminism - Ossome, Lyn (Feminist Africa, 2015)
Since the 1970s, informal work has expanded and appeared in new guises in the context of globalisation, neo-liberalism and migration, all of which are highly gendered processes (Chen et al. 2004; ILO 2002b, 2007a). An as yet unsettled question posed within feminist debates is whether women’s increased participation in informal economic activity contributes to their empowerment or their impoverishment (Meagher 2010). While economists have tended to see the informal economy as a source of economic opportunity for women in a sphere free of the gender-biased regulations of the formal economy (USAID 2005), more critical feminist and political-economy analyses have argued that the informal economy represents a poverty trap for women, concentrating them in low-skill, low-income activities with little prospect of advancement (Chant and Pedwell 2008; Chen et al 2006; Sassen 2002). Recent ILO research on gender and informal economies, and gender studies of global value chains offer gender analyses of wider global economic change processes, paying attention to informal labour markets, global commodity chains and transnational livelihood networks (Barrientos et al. 2003; Sassen 2002). These studies show that global and national economic changes have not limited women’s entry into labour markets, but rather incorporate them on unfavorable terms. Women are pushed into temporary and vulnerable employment within the informal economy, and excluded from more lucrative opportunities opened up by globalisation and liberalisation (Meagher 2010).
Keywords: State; Neoliberalism; Labour question; Pan-African feminism